Efektivitas Konsultasi Online di Puskesmas Pondok Betung Kota Tangerang Selatan - Varadella Kusumawardhani; Nida Handayani (Universitas 17 Agustus 1945 Semarang, Indonesia, 2024)
Online consultation is an idea from e-government in the health services sector that uses technology to integrate health services at Community Health Centers. The aim is to simplify bureaucratic processes in health services to the community. In practice, there are still several obstacles that arise, such as a lack of outreach efforts, slow response times from consultations, and recording that is not automatic because it still relies on WhatsApp. The aim of this research is to determine the effectiveness of